2015
DOI: 10.1007/s13149-015-0432-7
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis schistosomiasis: unusual lesion about two cases in Senegal

Abstract: Appendiceal schistosomiasis is a rare disease of only histopathological diagnosis. Appendectomy should be followed by treatment with praziquantel to avoid complications. We report two cases of appendiceal schistosomiasis while discussing the place of this infection in the pathogenesis of appendicitis. Finally we recommend a routine pathological examination of any part of appendectomy for better care for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…So after only 12 months of activity we identified 3 cases appendicitis bilharzia 51 histological studies performed or 5.9% of cases, our rate of completion of the pathological examination was 57.30%. In Senegal, in the Thiam study, after analysis of 3208 appendectomy over 10 years, he found 2 cases [14], in Mozambique on a series of 145 cases of appendicitis in Beira 13.1% or 9 cases were bilharzia appendicitis [7]. Similar work was carried out in Hong Kong, Ghana and Nigeria with frequencies of 0.2%, 2.4% and 2.9% respectively [14].…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…So after only 12 months of activity we identified 3 cases appendicitis bilharzia 51 histological studies performed or 5.9% of cases, our rate of completion of the pathological examination was 57.30%. In Senegal, in the Thiam study, after analysis of 3208 appendectomy over 10 years, he found 2 cases [14], in Mozambique on a series of 145 cases of appendicitis in Beira 13.1% or 9 cases were bilharzia appendicitis [7]. Similar work was carried out in Hong Kong, Ghana and Nigeria with frequencies of 0.2%, 2.4% and 2.9% respectively [14].…”
Section: Discussionmentioning
confidence: 79%
“…In Senegal, in the Thiam study, after analysis of 3208 appendectomy over 10 years, he found 2 cases [14], in Mozambique on a series of 145 cases of appendicitis in Beira 13.1% or 9 cases were bilharzia appendicitis [7]. Similar work was carried out in Hong Kong, Ghana and Nigeria with frequencies of 0.2%, 2.4% and 2.9% respectively [14].…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations